INTREGATION OF SOCIAL SCIENCE STUDIES AND MULTICULTURAL EDUCATION TO FIGHTING RASISME IN JUNIOR HIGH SCHOOL - Kartika, Nisa; Ni’mah, Zuma Hidayati; Suciati, Ratih (Jurnal Sosialita, 2025)
This research aims to describe (1) Learning that takes place in social studies subject in MTS Al-Iman Bulus Purworejo. (2) Implementation of social studies learning seen from the perpective of multicultural education in MTS 01 Al-Iman Bulus Purworejo, (3) The Learning of evaluation has seen from a multicultural on education perspective. This Research was conducted use descriptive qualitative methods and using a sace studi on MTS 01 Al-Iman Bulus Purworej. Data collection was cartied put use observation, interview, and documentation. Technique Data Analysis used by Miles and Huberman. This research resut obtained incude: (1) Sosial studied learning tnat takes in trough social interaction between teacher dan students. The teacher method is introducing history, culture, custom civil social diversity in Indonesia. (2) Implementation of multicultural education for student MTS 01 Al-Iman Bulus Purworejo has been emphasized by teacher since grade 7. Student are asked to look at diversity and case of global issues in Indonesia. (3) How to prevent racism in multicultural education and who respect each other cultural differences among student, because not all student come from the same city, but thet come from others cities.